2018
DOI: 10.1007/s40243-018-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of chemically synthesized SnO2-RuO2 mixed films

Abstract: The SnO 2 -RuO 2 mixed films are prepared by successive ionic layer adsorption and reaction (SILAR) method. The SnO 2 films combined with RuO 2 are prepared by varying the deposition cycles of SILAR. The effect of combining SnO 2 with RuO 2 on structural, morphological and electrochemical properties is studied. It is observed that the crystalline nature of SnO 2 changed to amorphous with increase in RuO 2 deposition cycles. The morphology is also changed from fibrous-porous to compact after increasing RuO 2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Since the SnO 2 adds only to the surface of the precursor spheres with the porosity, just a trace amount leads to a strong increase of C sp over the porous MnO 2 –Fe 3 O 4 . In recent days, research studies are now being devoted to making alternative electrodes including SnO 2 –Co 3 O 4 , SnS 2 –SnO 2 , SnO 2 –RuO 2 , etc. Special attention has been drawn toward these kinds of materials because they provide extraordinary energy densities from the Faradaic charge transfer compared to carbon-based materials.…”
Section: Metal Oxide-based Supercapacitorsmentioning
confidence: 99%
“…Since the SnO 2 adds only to the surface of the precursor spheres with the porosity, just a trace amount leads to a strong increase of C sp over the porous MnO 2 –Fe 3 O 4 . In recent days, research studies are now being devoted to making alternative electrodes including SnO 2 –Co 3 O 4 , SnS 2 –SnO 2 , SnO 2 –RuO 2 , etc. Special attention has been drawn toward these kinds of materials because they provide extraordinary energy densities from the Faradaic charge transfer compared to carbon-based materials.…”
Section: Metal Oxide-based Supercapacitorsmentioning
confidence: 99%
“…Redissolution of deposited films when exposed to solutions of the parent metal salts is a limitation especially in the case of oxides. [42,194] Lindroos et al have found that both the use of complexing agents and variation of the solution pH strongly affect the growth rate of zinc oxide films. [51] Tolstoy observed an effect of the salt concentration and suggested the use of metal precursors with a lower oxidation state for the deposition of MnO nanolayers.…”
Section: Fundamentals and Theoretical Backgroundmentioning
confidence: 99%
“…The interfacial charge transfer between Bi 2 O 3 , MnO 2 and graphite, and the nanomorphology enabled by the SILAR deposition have been highlighted as the key factor in obtaining good charge storage performances. Alternative composites, including NiO-ZnO, [192] ZnO-CdO, [193] and SnO 2 -RuO 2 [194] have been fabricated targeting potential uses in solar photovoltaics, sensors and supercapacitors, respectively. Ammonia complexes of Ni and Cd were adopted in the NiO-ZnO and ZnO-CdO depositions while ZnO was initially electrodeposited.…”
Section: Composite and Complex Oxidesmentioning
confidence: 99%
“…[19] Moreover, SnO 2 shares the rutile structure and lattice parameters with RuO 2 , making it a suitable choice for composite formation, thereby offering a promising avenue for improving SC performance while mitigating costs. [42][43][44] In this study, we utilized pulsed laser deposition (PLD) to synthesize thin film electrodes of SnO 2 , RuO 2 , and their composites on stainless steel-304 (SS-304) substrates using solid targets of SnO 2 and RuO 2 . We then fabricated a symmetric supercapacitor device (SSD) using a deposited SnO 2 -RuO 2 composite thin film as both positive and negative electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Moreover, SnO 2 shares the rutile structure and lattice parameters with RuO 2 , making it a suitable choice for composite formation, thereby offering a promising avenue for improving SC performance while mitigating costs. [ 42–44 ]…”
Section: Introductionmentioning
confidence: 99%